Polish technology parks: Towards 4th generation parks. Preliminary results of an empirical study - Kwieciński, Leszek (Journal of Public Governance, 2018)
The main research aim of the paper is to analyze the place and effects of technology parks and their function. The paper presents the concept of fourth generation technology parks. These parks, in addition to previous functions: innovation, incubation, promotion, and agglomeration, have three new functions: they foster civilization progress, help create networks, and support internationalization processes. It is obvious that the parks are not the crucial condition for creating innovative public policy, but they can act as an accelerator and a coordinator of pro-innovation processes. The paper mostly uses an empirical approach, presenting selected results of a nationwide research project financed by the National Science Centre of Poland. The study uses systemic analysis and the empirical method (PAPI) for primary data collection.